A unified quartet DNA gel electrophoresis instrument with integrated agarose gel casting, electrophoresis, staining, and imaging facilities. Issue 9 (7th July 2021) - Maurye, Praveen; Basu, Arpita; Kumari, Kavita; Dey, Priyanka; Sen, Sohini; Devi, Manoharmayum Shaya
Abstract: Agarose gel electrophoresis is the most useful and revolutionary process for separating, analyzing, identifying, and purifying different DNA fragments (in shape or size) from any cell or organism. This process is an amalgamation of four associated techniques viz. gel casting, electrophoresis, staining, and imaging, which are consecutively accomplished to get desired results. Various types of commercialized/non‐commercialized device and reagent kits are available with manufacturers to perform the associated techniques with simplicity. All these devices need secure space, separate operating procedures, and timely maintenance for the long run. In the absence of a low‐cost integrated electrophoresis device that can be utilized for the complete gel electrophoresis process, untimely operational failure of any individual equipment affects the experiment. In this paper, we describe an integrated gel electrophoresis instrument, which provides all facilities for agarose gel casting, electrophoresis, staining, and imaging techniques without any exposure to harmful chemicals. Construction of this four‐in‐one instrument in the laboratory requires off‐the‐shelf and pre‐existing components. Overall estimated cost is nearly US$ ∼222.00; and it can be assembled within 1 h, which makes it an inexpensive, user‐friendly, and effortless system. It has proved to be advantageous for researchers working in wide varieties of laboratories on the evaluation of nucleic acids.